Cultural Differences between American and Israeli Medical Students Regarding Their Perceptions of the Medical Profession and Satisfaction with Studies - Lotan, Eyal; Shenkman, Louis; Notzer, Netta (Canadian Medical Education Journal, 2010)
Background: Cultural differences have been discussed as a potential factor influencing students' perception and motivation towards their studies. At the Sackler Faculty of Medicine, Tel-Aviv University, two separate programs coexist for American and Israeli medical students. Both are taught at the same sites and by the same faculty, thus enabling cultural comparisons. Our aim was to examine the differences of two medical student groups, American and Israeli, regarding their satisfaction with studies, view of the educational workload, and their perceptions of physician characteristics. Methods: During the academic year 2007-2008 we administered an anonymous questionnaire to the two groups immediately after their first clinical clerkship in internal medicine. The response rate was 82% (90 out of 110) for the Israelis and 93% (53 out of 57) for the Americans. Results: Americans, compared to the Israelis, are significantly more satisfied with their medical studies, consider fewer alternatives to future careers in clinical medicine, feel less of a workload, and hold a more positive opinion of physician characteristics. Conclusions: Cultural differences affect students' perception of their studies, mentors and future careers. Medical educators should be sensitive to the effects of students' background which influence academic and professional attitudes and find ways to strengthen their commitment to the profession.